(untitled) (The Research of Medical Science Review, 2025)
Background: Postoperative pain management remains a critical aspect of surgical care, significantly impacting patient recovery and satisfaction. Multimodal analgesia, which combines different analgesic techniques and agents, has been increasingly advocated as an effective strategy for managing postoperative pain, minimizing opioid use, and reducing associated complications. Aim: This study aimed to evaluate the effectiveness of multimodal analgesia in improving postoperative pain outcomes among surgical patients. Methods: This retrospective cohort study was conducted at ayub teaching hospital abbottabad, from September 2023 to August 2024. Fifty patients who underwent elective surgical procedures and received multimodal analgesia were included. Data on demographic variables, pain scores (measured on the Visual Analog Scale), opioid consumption, and the incidence of adverse events were collected from medical records. Comparative analyses were performed to evaluate outcomes against a control group receiving conventional analgesia. Results: Patients in the multimodal analgesia group reported significantly lower pain scores at 6, 12, and 24 hours postoperatively compared to the control group (p < 0.05). Opioid consumption was reduced by 35% in the multimodal group, with fewer opioid-related adverse effects such as nausea and sedation. Additionally, patients demonstrated faster mobilization and shorter hospital stays, with a mean difference of 1.2 days compared to the control group. Conclusion: Multimodal analgesia proved to be an effective approach for postoperative pain management, offering better pain control, reduced opioid reliance, and fewer adverse effects. Its adoption in clinical practice could enhance patient recovery and overall surgical outcomes.